Assessment of Salivary stress marker in Completely Edentulous Patients and Its association with Residual Ridge Resorption: A cross sectional study - Sinha, Divyansh; Maiti, Subhabrata; J, Selvaraj; P, Jessy; Vaishnavi, Allour (Journal of Neonatal Surgery, 2024)
AIM & BACKGROUND: Residual ridge resorption (RRR) is an ongoing inflammatory process that can result in tissue damage, particularly through the formation of free radicals, which can lead to bone resorption via various pathways and mechanisms. The aim of this study was to assess and explore the connection between cortisol levels, a stress marker found in saliva, and the extent of residual ridge resorption in individuals who are completely edentulous, with or without dentures. METHODS:In this research, a total of 60 participants between the ages of 45 and 70, who had no natural teeth, were included. Saliva samples were gathered in sterile containers. The mean levels of cortisol were evaluated using ELISA kit and radiographic examination of remaining bone level at the mental foramen region was assessed. To analyze the data, we employed an independent t-test to compare two groups: those who wore dentures and those who did not. Additionally, we conducted Pearson and Spearman correlation analyses within the SPSS software to evaluate the potential relationship between cortisol levels and bone loss. RESULTS: The findings indicated a notable reduction in cortisol levels, a salivary stress marker, among patients who wore dentures in comparison to those who did not wear dentures (p=0.001).The strong negative correlation (-0.81 & -0.94) was found between cortisol and residual bone. CONCLUSION: Cortisol levels exhibited a notable reduction in individuals wearing dentures as opposed to those without dentures. Concurrently, long-term denture wearers experienced a decrease in residual ridge resorption, which suggests a decrease in stress markers and subsequently less pronounced residual ridge resorption. CLINICAL SIGNIFICANCE : The use of dentures may contribute to reduced cortisol levels and less residual ridge resorption in long-term wearers, potentially indicating improved oral health and reduced stress-related oral changes leading to a great situation for implant too..